Analisis Kepemimpinan Berbasis Keterampilan Terhadap Etos Kerja Karyawan Di PT. Sumatera Hakarindo - Andreas Baginda Simorangkir; Hendra Jonathan Sibarani (CERED Indonesia Institute, 2022)
This study aims to determine skill-based leadership on the work ethic of employees in taking action whether leadership can be able to motivate employees to do something beyond the target. In addition, the skills of the company's leadership must be able to improve the work ethic of employees if the leader is willing to explain the tasks and plans of the work equipment both individually and in groups and the company's leaders must be able to provide information about the tasks, goals, and intentions in order to formulate plans in order to achieve the goals carried out properly. The purpose of this discussion is to find out how transformational leadership on leadership skills, analyze skill-based effectiveness on work ethic and analyze leadership success in improving work ethic. The results show that PT Sumatera Hakarindo has implemented a skills-based leadership system in work ethic where all work is done well in transformational leadership, skill-based effectiveness on work ethic and leadership success in improving work ethic.